(untitled) (Research, Society and Development, 2020)
During the last decades, researchers have been growing the interest in surface treatment with an antimicrobial agent. Silver nanoparticles (AgNPs) are widely used in biomedical fields due to their potent antimicrobial activity. So, in this study was investigated silver particles (isles) coated on titanium surface for dental and orthopedic application. Silver particles coating process on titanium surface were performed via sputtering that is a plasma-assisted deposition technique with and titanium without treatment was applied as comparing standard. Plasma treatment parameters were optimized so that the result was not a thin film of Ag but dispersed particles of Ag on the Ti-cp surface. The alloy surfaces were investigated using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). In order to investigate antibacterial potential Staphylococcus aureus and Escherichia coli have been used at Agar diffusion assay. The results were analyzed by analysis of variance (ANOVA) in order to verify significant difference antimicrobial activity between samples that have shown no difference between the surfaces studied treatments. For silver deposition scattered particles (isles) over titanium surface for a 10-minute treatment, EDS revealed by silver clusters that the particles were not properly scattered onto surface, hence, the low effectiveness in antibacterial activity.